Thermal Instability Induced Oriented 2D Pores for Enhanced Sodium Storage - Kong, Lingjun; Xie, Chen‐Chao; Gu, Haichen; Wang, Chao‐Peng; Zhou, Xianlong; Liu, Jian; Zhou, Zhen; Li, Zhao‐Yang; Zhu, Jian; Bu, Xian‐He (Small (Weinheim an der Bergstrasse, Germany), 2018)
Hierarchical porous structures are highly desired for various applications. However, it is still challenging to obtain such materials with tunable architectures. Here, this paper reports hierarchical nanomaterials with oriented 2D pores by taking advantages of thermally instable bonds in vanadium‐based metal–organic frameworks (MOFs). High‐temperature calcination of these MOFs accompanied by the loss of coordinated water molecules and other components enables the formation of orderly slit‐like 2D pores in vanadium oxide/porous carbon nanorods (VOx/PCs). This unique combination leads to an increase of the reactive surface area. In addition, optimized VOx/PCs demonstrate high‐rate capability and ultralong cycling life for sodium storage. The assembled full cells also show high capacity and cycling stability. This report provides an effective strategy for producing MOFs‐derived composites with hierarchical porous architectures for energy storage. A unique bonding guidance in vanadium‐based metal–organic frameworks is investigated for achieving oriented 2D pores. Benefiting from its typical loose morphology, the hierarchical vanadium oxide/porous carbon composite with oriented pores endows sodium‐ion anode with superior electrochemical performance.